A PSYCHOMETRIC TOOL TO MEASURE THE GENERATIONAL DIFFERENCES: DEVELOPMENT AND STANDARDIZATION OF PSYCHOSOCIAL WELL-BEING SCALE FOR ELDERLY - Soumya Kammar; Jinamoni Saikia (PEOPLE: International Journal of Social Sciences, 2026)
With the increasing global attention on ageing population, assessing psychosocial well-being among elderly has become essential for ensuring holistic care and age specific interventions. Besides, every generation carries its own psychological imprint shaped by the decades they have lived through. As a result, understanding well-being in old age requires assessment approaches that are sensitive to generational contexts and life-course experiences. However, culturally relevant standardized tools for such assessment are limited, especially in age inclusiveness. The present study introduces the Psychosocial Well-Being Scale for Elderly (PSWSE), a five-point Likert comprehensive scale developed to measure well-being of elderly in nine dimensions as Psychological Resilience (PR), Cognitive Functioning (CF), Emotional Wellness (EW), Financial Autonomy (FA), Cultural Engagement (CE), Spiritual Wellness (SW), Physical Wellness (PW), Subjective Well-Being (SWB), and Interpersonal Relationships (IR). The scale consists of 60 items and was standardized after employing on a diverse sample of 466 elderly individuals aged 60 years and above. This scale was developed through systematic psychometric procedures including expert validation, item analysis and exploratory factor analysis, yielding high reliability (Cronbach’s a = 0.898) and sampling adequacy (KMO = 0.828, Bartlett’s χ² = 2645.867, p < 0.001). The inter-dimension correlations ranged from 0.080 to 0.818, indicating moderate relationships among the nine dimensions, suggesting these constructs are strongly related yet theoretically distinct. The determinant score of the correlation matrix is 0.034> 0.00001, which confirms that there is an absence of multicollinearity and severe redundancy among dimensions. Reliability of the full scale was established through Split-Half method (even-odd items:0.831) by applying the Spearman-Brown formula. Test-retest reliability conducted on a subset of 150 participants, demonstrating excellent temporal stability of Psychosocial well-being scale and its nine dimensions (r = 0.92). To explore its community level applicability, the standardised scale was employed in the study and administered on a separate sample of 240 respondents across two generational groups i.e. baby boomers and silent generation. The results revealed that baby boomers reported better psychological well-being in most domains, including mental wellness, cognitive functioning, economic independence, cultural practices, physical wellness and subjective well-being. In contrast, the silent generation displayed comparatively greater emotional and spiritual wellness, possibly due to deeper life reflection and stronger ties to traditional belief systems. This study offers a statistically validated scale that not only contributes to accurate assessment of psychosocial well-being among the elderly but also provides meaningful generational insights. The findings have practical implications for designing targeted mental health strategies, elder care policies and age-sensitive and age-inclusive interventions to support positive and active ageing.